Population Pharmacokinetics of Inhaled Tobramycin Powder in Cystic Fibrosis Patients. (12th February 2014) - Ting, L; Aksenov, S; Bhansali, SG; Ramakrishna, R; Tang, P; Geller, DE
Abstract : Tobramycin powder for inhalation (TOBI Podhaler or TIP) is approved for the treatment of Pseudomonas aeruginosa airway infection in patients with cystic fibrosis (CF). A population pharmacokinetic model for tobramycin inhalation powder (TIP) in CF patients was developed to characterize the effect of covariates including body mass index (BMI) and lung function (forced expiratory volume in 1 s as percent of the predicted value (FEV1 % predicted) at baseline) on the serum exposure parameters. A two‐compartment model with first‐order elimination and first‐order absorption was developed. Across a range of baseline demographic values in the study population, the predicted mean values for the maximum ( C max ) and trough ( C trough ) plasma concentrations at steady state were at least 7.5 and 5‐fold lower, respectively, than the recommended thresholds for tobramycin toxicity (12 µg/ml for C max and 2 µg/ml for C trough ). This model adequately described the tobramycin serum concentration–time course in CF patients following inhalation of TIP. The results indicate that no BMI‐ or FEV1 ‐based dose adjustment is needed for use of TIP in CF patients. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e99; doi:10.1038/psp.2013.76 ; published online 12 February 2014